Engineering geological mapping - Griffiths, J. S. (Land Surface Evaluation for Engineering Practice, 2001)
Introduction The development, scope and examples of best practice in the preparation of geological maps and plans for engineering practice are discussed in detail in Dearman (1991), and this remains the definitive British text on the subject. In the UK engineering geological maps were recognized as forming a significant component of site investigations with the publication of the Geological Society Working Party Report on maps and plans (Anon. 1972). In many parts of the world the practice is also long established (e.g. Peter 1966; Popov et al. 1950), and in 1976 UNESCO produced a guide for the preparation of engineering geological maps (Anon. 1976). Many examples of international studies were reported at the 1979 IAEG Newcastle Symposium on Engineering Geological Mapping. In contrast, in the United Kingdom, BS5930, the Code of Practice for Site Investigations, which was first published in 1981 and has guided the scope and content of site investigations in the UK for the past two decades, makes scant reference to geological or engineering geological mapping (Griffiths & Marsh 1986). As noted in Griffiths & Edwards (2001), this situation has not been corrected in the revision of BS5930 published in 1999. Fookes (1997), in the first Glossop lecture, states ‘that engineering geological mapping, even sketch mapping, is particularly under used in British practice’, and this is despite its longstanding and successful track record (Dearman & Fookes 1974). As with many facets of land surface evaluation, this situation needs to be addressed. The distinction between engineering geological maps and plans